Tooth Profile Design of Tri-arc Harmonic Gear Drive - Xiao Jichang; He Xiaofei; Yang Yong; Wang Jiaxu; Huang Yanyan; Zhou Qinghua (Jixie chuandong)
Based on the exact conjugate method of harmonic gear drive， the tooth profile design method of the tri-arc harmonic gear drive is proposed and the influence of flex spline profile parameters on the conjugate interval are studied. The research results show that the tri-arc harmonic gear drive has a wider conjugate zone and a smaller interval between conjugate zones than the double circular arc harmonic drive. Reducing the radius of the convex tooth profile is helpful to increase the conjugate zone, but not conducive to reduce the interval between conjugate zones. Reducing the radius of the intermediate arc, the angles and are help to increase the conjugate zone, and also to reduce the interval between conjugate zones. The radius of the concave profile has little effect on the actual conjugate zone. Appropriate profile parameters of flex spline can bring a wider conjugate zone and shrink the interval between conjugate zones, which may facilitate the conjugate contact between the teeth as well as the improvement of transmission accuracy and torsional stiffness of harmonic drive.